2011
DOI: 10.3109/09638288.2011.563821
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing return to work experienced by people with acquired brain injury: a qualitative research study

Abstract: Different aspects were experienced as being important during the process of RTW after ABI. These aspects should be kept in mind during the process of RTW to make the outcome as successful as possible. It is advised to pay special attention to the recovery opportunities of an individual, to inform the employer, colleagues, occupation physician and the occupational specialist about ABI, and to support people with ABI for long time periods. An important role can be played by the rehabilitation centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 20 publications
8
39
0
Order By: Relevance
“…All studies demonstrated triangulation except for six [54,[59][60][61][62][63]. Only 10 of the 37 studies did not describe the ICF in detail in the introduction [48,50,53,56,57,[64][65][66][67][68]. Twenty-seven studies described the ICF in detail, giving the reader a sound understanding of the framework.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies demonstrated triangulation except for six [54,[59][60][61][62][63]. Only 10 of the 37 studies did not describe the ICF in detail in the introduction [48,50,53,56,57,[64][65][66][67][68]. Twenty-seven studies described the ICF in detail, giving the reader a sound understanding of the framework.…”
Section: Resultsmentioning
confidence: 99%
“…Just under half the studies used the ICF during data collection by asking the participants open-ended questions reflecting the ICF components [48,50,51,53,55,56,60,63,[76][77][78][88][89][90][91][92] or asking for facilitators and barriers related to each component [67] (Table 4). Eight of these studies used six common questions based on the ICF components [48,51,56,77,78,90,92,93] (see Appendix A for questions).…”
Section: Context Of Icf Usementioning
confidence: 99%
See 1 more Smart Citation
“…However, despite clear descriptions of the models themselves, a lack of high quality evaluations and dearth of RCTs with robust economic evaluations means evidence to support their effectiveness or cost-effectiveness is weak [29,30]. The strongest evidence favours an individually-tailored, case-coordination approach [31,32] with early intervention to optimize employment outcomes [30,31,[33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies discuss the important relationship between having strong informal support and returning to employment (Izaute et al 2008;van Velzen et al 2011). Being involved in productive activity, such as work or study has been found to be an important determinant in the facilitation of the use of natural community supports.…”
Section: Barriers To Re-integrationmentioning
confidence: 99%